Directly printed stretchable strain sensor based on ring and diamond shaped silver nanowire electrodes1. Issue 36 (23rd April 2015) - Lee, Hyungdong; Seong, Baekhoon; Moon, Hyungpil; Byun, Doyoung
<x xml:space="preserve">Abstract</x> Printing Ag NWs/PDMS composite strain gauge. The Ag NWs networks were formed just on top of the PDMS layer.